Ankle tendoscopy: state of the art. Issue 6 (27th September 2017) - Pereira, Helder; Vuurberg, Gwendolyn; Stone, James; Lui, Tun Hing
Abstract : Tendon disorders may be caused by a wide range of pathologies, including (partial) tendon tears, tendinitis, tendinosis and tenosynovitis. Endoscopic techniques have been developed to address these pathologies and have been optimised over the years. Currently, these techniques are mainly used to address disorders of the Achilles tendon, flexor hallucis longus (FHL) tendon, peroneal tendons and the posterior tibial tendon. It is important to perform a thorough history and physical examination in order to define symptom intensity and factors that exacerbate symptoms, and to define the site of maximal local tenderness. This is in order to decide on appropriate options for assessment and treatment. Tendoscopy is currently accepted as a useful therapeutic alternative in cases of failed conservative treatment. The main accepted indications for tendoscopy include FHL, Achilles and peroneal pathology, posterior tibial tendinopathy, and retrocalcaneal bursitis. Complication rates for the procedure are low despite the proximity of neurovascular structures, and tendoscopy is regarded as a safe and effective procedure in the treatment of tendon pathology.